PENGARUH KASUS COVID-19, KAPITALISASI PASAR, MARKET BOOK RATIO, DAN PROFITABILITAS TERHADAP STOCK RETURN - Muryadi, Phoebe; Suhendah, Rousilita (Jurnal Paradigma Akuntansi, 2024)
The purpose of this study is to analyze the effect of Covid-19 cases, market capitalization, market book ratio, and profitability on daily stock returns in property and real estate and telecommunications sector companies listed in Indonesia Stock Exchange during 2020. This study uses 29 samples, which were selected by purposive sampling method with a total observation of 5,800 data. The research data was collected and calculated using Microsoft Excel 2013 program and then processed with multiple regression analysis using the Eviews 9.0 program. The results of this study prove that the Covid-19 case and the market book ratio have a significant effect on stock returns, while market capitalization and profitability have no significant effect on stock returns. The implication of this research is to become a consideration for investors to see the condition of the company's shares not only from its financial statements, but also to see other factors that can affect the condition of the company's shares. For companies, it is necessary to improve their financial health in order to convince investors to consider investing.